The evolving partnership between the Government of Ghana and national faith-based health providers: leadership perspective and experiences from the Christian Health Association of Ghana. Issue 5 (4th July 2017) - Yeboah, Peter; Buckle, Gilbert
ABSTRACT: The imperative for partnership between government and non-state actors to achieve the health-related targets of the Sustainable Development Goals (SDGs) highlights the interconnections and interdependence of health systems. The Christian Health Association of Ghana (CHAG) has had an evolving partnership with the Government of Ghana in promoting universal health coverage. This viewpoint reflects on CHAG's current and past leadership experiences and approaches that have guided this partnership model, with a view to sharing lessons with various church health associations in Africa. It highlights the need for faith-based health providers to uphold both Christian values and professionalism in promoting sustainable partnership with government in health service provision.